1995
DOI: 10.1006/excr.1995.1126
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Localization of the Interferon-Inducible Protein Kinase PKR in Human Cells and Transfected Mouse Cells

Abstract: The levels and subcellular distribution of the interferon-inducible double-stranded RNA-dependent protein kinase PKR have been measured in human Daudi cells and stably transfected mouse NIH 3T3 cells expressing the human protein kinase. Immunofluorescence of intact cells and quantitative immunoblotting of cell extracts indicate that PKR occurs in both the cytoplasm and the cell nucleus, with staining specifically in the nucleolus. The ratio of cytoplasmic to nuclear PKR is approximately 5:1 in control cells; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
92
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 41 publications
(52 reference statements)
11
92
0
Order By: Relevance
“…There are limited data concerning the movement of PKR within the cell in response to viral infection. While adenovirus infection and interferon treatment do not alter PKR localization (40,41), infection of interferon-treated HeLa cells with encephalomyocarditis virus (EMCV) results in the displacement of PKR from ribosomal subunits and the aggregation of PKR in the perinuclear area (30). However, the PKR that aggregates in the perinuclear area during EMCV infection is activated and is thought to contribute to the inhibition of EMCV replication (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data concerning the movement of PKR within the cell in response to viral infection. While adenovirus infection and interferon treatment do not alter PKR localization (40,41), infection of interferon-treated HeLa cells with encephalomyocarditis virus (EMCV) results in the displacement of PKR from ribosomal subunits and the aggregation of PKR in the perinuclear area (30). However, the PKR that aggregates in the perinuclear area during EMCV infection is activated and is thought to contribute to the inhibition of EMCV replication (30).…”
Section: Discussionmentioning
confidence: 99%
“…While PKR is normally found predominantly in the cytoplasm, it is also present in lower quantities in the nucleolus, where it is thought, although not proven, to play a role in ribosome biogenesis (40,41). Additionally, there is indirect evidence implicating PKR in the transcriptional up-regulation of select genes in response to viral infection or dsRNA (75), and PKR has been demonstrated to directly interact with several proteins present in the nucleus that may affect regulation of the cell cycle (22,23,55).…”
Section: Discussionmentioning
confidence: 99%
“…However, electron micrograph analysis and immunogold labeling has also indicated that a fraction of PKR resides in the nucleus (48,49). Since the NFARs have a consensus bipartite nuclear localization signal (Fig.…”
Section: Isolation and Identification Of Nfar-1 And -2-mentioning
confidence: 99%
“…8,13,14 Although PKR has been identified in nuclear and cytoplasmic fractions, most activities attributed to PKR occur in the cytoplasm; hence, the role of nuclear PKR has remained unclear. Jeffrey et al 15 found, in NIH3T3 cells overexpressing exogenous PKR and Daudi Burkitt's lymphoma cells treated with interferon, the ratio of cytoplasmic to nuclear PKR to be 5:1. Both nuclear and cytoplasmic PKR were reported to be 68 kDa; the only difference was in post-translational modification (PTM).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, cytoplasmic PKR presented with multiple isoelectric points (pIs), nuclear PKR presented with a single, basic pI, suggesting this protein was not highly phosphorylated. 15 Recent studies have attributed clinical and pathological significance to nuclear PKR. 9,13,16 We initially reported that CD34 þ cells from myelodysplastic syndrome (MDS) patients contain elevated levels of p-T451 PKR as compared with controls.…”
Section: Introductionmentioning
confidence: 99%